Isolation and structural elucidation of compounds from the non-alkaloidal extract of Nicandra physaloides and the antimicrobial activity of withanicandrin. (The East and Central African Journal of Pharmaceutical Sciences, 2018)
The aerial parts of Nicandra physaloides plant collected from Kenyatta National Hospital grounds were dried and subjected to acid-base extraction and partitioned to obtain alkaloidal and non-alkaloidal extracts. The non-alkaloidal extract yielded three compounds; withanicandrin, β-sitosterol and stigmasterol after column chromatography. Withanicandrin exhibited antifungal activity against Saccharomyces cerevisiae and Candida albicans but lacked antibacterial activity.
Keywords: Nicandra physaloides; withanicandrin; β-sitosterol; stigmasterol; antifungal activity